2005
DOI: 10.1159/000086984
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Multidrug Resistance Proteins as a Predictor of Poor Response to Chemotherapy and Prognosis in Patients with Nodal Diffuse Large B-Cell Lymphoma

Abstract: Background/Aims: The aim of this study was to determine whether expression of P-glycoprotein (P-gp), multidrug-resistance-related protein 1 (MRP1), and lung resistance protein (LRP) was related to the response to induction chemotherapy and prognosis in untreated diffuse large B-cell lymphoma (DLBCL). Methods: We assessed immunohistochemical expression of P-gp, MRP1 and LRP, using formalin-fixed and paraffin-embedded specimens of lymph node in 41 patients with DLBCL. Association between expression of these thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 64 publications
7
29
1
1
Order By: Relevance
“…In human medicine P-gp expression has been observed mainly in cutaneous T-cell lymphomas (Jillella et al 2000), nasal NK/T lymphomas (Saglam et al 2008), acute lymphoblastic leukemia (ALL) (Plasschaert et al 2003), chronic lymphocytic leukemia (Jamroziak et al 2004) and DLBCL (Ohsawa et al 2005). In our study positive P-gp labeling was observed in LBL, CBL, BLL and CB/CCL.…”
Section: Discussionsupporting
confidence: 59%
“…In human medicine P-gp expression has been observed mainly in cutaneous T-cell lymphomas (Jillella et al 2000), nasal NK/T lymphomas (Saglam et al 2008), acute lymphoblastic leukemia (ALL) (Plasschaert et al 2003), chronic lymphocytic leukemia (Jamroziak et al 2004) and DLBCL (Ohsawa et al 2005). In our study positive P-gp labeling was observed in LBL, CBL, BLL and CB/CCL.…”
Section: Discussionsupporting
confidence: 59%
“…MRP1 functions similarly to MDR1 in reducing tumor sensitivity to chemotherapy, and it can recognize and pump out chemotherapy drugs bound to glutathione in tumor cells. High expression of MDR1 and MRP1 in different types of B cell lymphoma tissues has been associated with poor response to chemotherapy (25). Thus, our finding, that Mda-7/IL-24 overexpression downregulated MDR1 and MRP1 expression in Raji and Daudi cells, suggests that Mda-7/IL-24 may enhance the intracellular accumulation of anticancer drugs.…”
Section: Discussionmentioning
confidence: 59%
“…The overexpression of major vault protein (MVP), also called lung resistance (-related) protein (LRP/LRRP), in the cured cohort was unexpected because expression of this protein on tumour cells has been associated with chemotherapy resistance in DLBCL (Ohsawa et al, 2005). However, in this study, MVP/LRRP was mainly expressed by the tumourinfiltrating reactive cells and mightin this positionhave a different function (Schroeijers et al, 2002).…”
Section: Discussionmentioning
confidence: 62%